Sensitivity of Larvae and Adult and the Immunologic Characteristics of Litopenaeus vannamei under the Acute Hypoxia - Hailong Zhou; Yuhu Li; Lin Wei; Zhihuai Zhang; Hao Huang; Xiaoping Diao; Jianhai Xiang (Journal of Chemistry)
Litopenaeus vannamei is one of the most commercially important species of shrimp in the world. In this study, we performed acute hypoxia tests with Litopenaeus vannamei to estimate 12 h median lethal concentration (LC50) values at different life stages. The results indicated that the 12 h LC50 values were significantly different in different life stages of shrimp (P<0.05). The maximum value of 12 h LC50 was 2.113 mg L−1 for mysis III, and the minimum value was 0.535 mg L−1 for adult shrimp with an average total length of 6 cm. The study also determined the hemocyanin concentration (HC) and the total hemocyte counts (THC) in the conditions of hypoxia and reoxygenation. These results showed that the THC decreased and the HC increased under hypoxia, and the THC increased and the HC decreased in the condition of reoxygenation. These results can provide fundamental information for shrimp farming and seedling and also can guide the breeding selection, as well as being very helpful to better understand the hypoxia stress mechanism of shrimp.